(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2025)
This study aims to analyze the time series of population in the Kingdom of Saudi Arabia during the period 1950–2024 using Box-Jenkins (ARIMA) models, with the objective of forecasting population trends up to 2030. The analysis was conducted using SPSS version 27, following the Box-Jenkins methodology which includes identification, estimation, diagnostic checking, and forecasting. Several ARIMA models were tested, including ARIMA (1,1,1) and ARIMA (2,1,2); however, the results indicated that the most suitable model was ARIMA (3,1,2). This model achieved the highest R-squared value (0.963), the lowest BIC, and produced residuals with no significant autocorrelation. The model demonstrated excellent forecasting accuracy, and residual analysis confirmed its adequacy. The study recommends adopting the ARIMA (3, 1, 2) model as a reliable forecasting tool for population planning and policy formulation.